1998
DOI: 10.1037/1089-2699.2.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of individual and group psychotherapy: A meta-analytic perspective.

Abstract: Recent reviews of the group psychotherapy literature indicate that group is a beneficial and cost-effective treatment format. However, collective findings on the differential efficacy of group when compared with individual therapy remain problematic, incomplete, or controversial. To remedy this problem, the authors conducted a meta-analysis of 23 outcome studies that directly compared the effectiveness of the individual and group therapy formats when they were used within the same study. Results were consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(130 citation statements)
references
References 56 publications
8
118
0
4
Order By: Relevance
“…However, research on adult depression treatment (e.g., Hollon, 2000;Jacobson et al, 1996;Jacobson, Martell, & Dimidjian, 2001) has raised questions about whether a cognitive emphasis is needed to generate improvement and even whether cognitive intervention adds significantly to such noncognitive approaches as behavioral activation. Promising results of some recent youth depression trials that used treatments without a cognitive emphasis suggest that this Burlingame, & Hoag, 1998); and study characteristics (study attrition rates, whether studies were peer-reviewed, and whether outcomes were assessed via youth self-report vs. parent report; see, e.g., Hammen & Rudolph, 1996). These analyses, although not addressing our six primary aims, were useful in delineating the boundary conditions within which psychotherapy is beneficial.…”
Section: Are Treatments That Emphasize Changing Cognitions More Effecmentioning
confidence: 99%
“…However, research on adult depression treatment (e.g., Hollon, 2000;Jacobson et al, 1996;Jacobson, Martell, & Dimidjian, 2001) has raised questions about whether a cognitive emphasis is needed to generate improvement and even whether cognitive intervention adds significantly to such noncognitive approaches as behavioral activation. Promising results of some recent youth depression trials that used treatments without a cognitive emphasis suggest that this Burlingame, & Hoag, 1998); and study characteristics (study attrition rates, whether studies were peer-reviewed, and whether outcomes were assessed via youth self-report vs. parent report; see, e.g., Hammen & Rudolph, 1996). These analyses, although not addressing our six primary aims, were useful in delineating the boundary conditions within which psychotherapy is beneficial.…”
Section: Are Treatments That Emphasize Changing Cognitions More Effecmentioning
confidence: 99%
“…Meta-analytic research (Burlingame, Fuhriman, & Mosier, 2003;Horne & Rosenthal, 1997;McRoberts, 1998;Smith, Wood, & Smale, 1980) and more specific studies (e.g., Toseland & Siporin, 1986) suggest that, in general terms, the group format is at least as effective as individual work in the alleviation of personal and interpersonal difficulties.…”
Section: A Brief Typology Of Therapeutic Groupworkmentioning
confidence: 99%
“…For example, some research has found group psychotherapy as effective as individual interventions in addressing clinically significant mental health problems (Burlingame, 2010;McRoberts, Burlingame & Hoag, 1998), and it has been claimed that increased group cohesion can be linked to improved overall outcomes in psychotherapy group setting (MacKenzie & Tschuschke, 1993). However, other studies argue that individual approaches have greater efficacy and lower drop-out rates (Cuijpers, van Straten & Warmerdam, 2008).…”
Section: Introductionmentioning
confidence: 99%